An Overview of Bee Keeping in Rupandehi District, Nepal over Seven Years - Khanal, Dipak; KC, Rabin; Neupane, Shankar (Nepalese Journal of Agricultural Sciences, 2025)
Beekeeping is a high-value income-generating agricultural activity in Nepal. However, there is a lack of intensive information related to beekeeping. We conducted a comparative study among the beekeepers in 2014 and 2021 to assess the status of bee keeping in a gap of seven years in Rupandehi district. Result revealed a slight increase in honey production averaging 21.35 and 25.45 kg/ year/hive in 2014 and 2021, respectively. The average number of beehives per beekeeper increased from 39 in 2014 to 42 in 2021. We report that primary bottlenecks to beekeeping are lack of foraging area, pesticide poisoning, pests, diseases, and lack of government subsidiary. The lack of foraging area was mainly attributed to rapid population growth and unplanned urbanization. The problem of pesticide intoxication was found to worsen during 7 years in the study area. Governmental incentives to beekeepers, and stricter rules on pesticide application could encourage beekeepers to get involved in bee keeping. Rigorous documentation on beekeeping can help realize the potential of honey production, and to come up with efficient mitigation measures towards problems associated in beekeeping.